HYDRAULIC CALCULATION OF THE STOCK PART OF THE BUILDING WATER SUPPLY SYSTEM (Modern education and development, 2025)
This article describes the methods of hydraulic calculation of the riser section of the internal sewage system of a building. The riser is the main element that vertically lowers the wastewater from sanitary and technical devices in multi-storey buildings. The calculation process takes into account the number of devices, conditional load (DU), waste flow, riser diameters and ventilation requirements. The article analyzes the conditions necessary for the effective operation of the system using calculation formulas, tables and calculation examples based on standard norms. Properly performed hydraulic calculation ensures safe, long-term and noise-free operation of the sewage system.